Immunotherapy-Based Targeting and Elimination of Leukemic Stem Cells in AML and CML - Valent, Peter (Int J Mol Sci, 2019)
The concept of leukemic stem cells (LSC) has been developed with the idea to explain the clonal hierarchies and architectures in leukemia, and the more or less curative anti-neoplastic effects of various targeted drugs. It is now widely accepted that curative therapies must have the potential to eliminate or completely suppress LSC, as only these cells can restore and propagate the malignancy for unlimited time periods. Since LSC represent a minor cell fraction in the leukemic clone, little is known about their properties and target expression profiles. Over the past few years, several cell-specific immunotherapy concepts have been developed, including new generations of cell-targeting antibodies, antibody–toxin conjugates, bispecific antibodies, and CAR-T cell-based strategies. Whereas such concepts have been translated and may improve outcomes of therapy in certain lymphoid neoplasms and a few other malignancies, only little is known about immunological targets that are clinically relevant and can be employed to establish such therapies in myeloid neoplasms. In the current article, we provide an overview of the immunologically relevant molecular targets expressed on LSC in patients with acute myeloid leukemia (AML) and chronic myeloid leukemia (CML). In addition, we discuss the current status of antibody-based therapies in these malignancies, their mode of action, and successful examples from the field.